(untitled) (Research, Society and Development, 2020)
Weeds have a great abundance in vegetable cultivation, being able to shelter pest insects and their natural enemies. The objective was to understand the ecological interactions between weeds and the entomofauna in the agroecosystem, based on this premise and the scarcity of studies on organic vegetable crops. In the Agreste region of Alagoas, Northeast Brazil, insects and weeds were collected for the development of phytosociological, faunal analysis of insect families and Pearson’s correlation in the incidence of insects in vegetables and weeds, along with meteorological factors. Nine weed species were identified, distributed in seven families. The number of insects collected was the same in weeds and vegetables, the predominant families in vegetables were Coccinellidae, Aphididae and Formicidae, whereas in weeds there were only the last two. When dealing with diversity, wealth and fairness, it was observed that in vegetables the values ​​are higher. Entomofauna in relation to meteorological factors did not show significant difference (p>0.05). The data obtained may assist future studies regarding the potential for insect hosting in weeds, in addition, it is also possible to study the biological control capacity with Coccinellidae, which was a predominant family in vegetables, and can assist in integrated pest management.